TISSUE CHANGES IN THE GUT OF ARAPAIMA GIGAS (SCHINZ, 1822), INFECTED BY THE NEMATODE SPIROCAMALLANUS INOPINATUS (TRAVASSOS, 1929) - León Gaines, Angélica Patricia (2012)
The Arapaima gigas (Schinz, 1822) is a species that inhabits the Amazonian rivers that has a great ecological importance. For its high commercial value and overfishing, the Arapaima has a risk of extinction. For this reason, it is attractive for fish farming, apart from having a good zoo-technical performance. One of the most serious problems to its production in cultivation is the parasitic diseases which intervene in the quantity and quality of fish. The endoparasites such as nematodes feed on nutrients already processed by the host and can cause intestinal disorder, bringing the fish malnutrition and a state of anemia. In the present study, the histopathological changes caused in the gut of A. gigas by the nematode Spirocamallanus inopinatus (Travassos, 1929) were analyzed. The intestines of six specimens of which three hosts were parasitized by nematodes were histological processed. The following changes were found: focal areas of necrosis, desquamation, inflammatory infiltrate, cytolysis and formation of fibrous capsules. This is the first study which reports the tissue lesions in the intestine of A. gigas caused by the nematodes S. inopinatus.